2013
DOI: 10.1080/10691898.2013.11889657
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Faculty Views of Statistics and Student Preparation Beyond an Introductory Class

Abstract: The purpose of this research is to better understand the role of statistics in teaching and research by faculty from all disciplines and their perceptions of the statistical preparation of their students. This study reports the findings of a survey administered to faculty from seven colleges and universities regarding the use of statistics in teaching and research with undergraduate students. The introductory statistics course serves as a foundation for statistical methods that students learn and use in classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…At this point, raising individuals with statistical literacy emerges as an important goal. Doehler, Taylor and Smith (2013) investigated to understand the role of statistics in teaching and research by faculty from all disciplines and their perceptions of the statistical preparation of their students. They administered a survey to 747 faculty members from seven colleges and universities regarding the use of statistics in teaching and research with undergraduate students.…”
Section: Theoretical Framework Statistical Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, raising individuals with statistical literacy emerges as an important goal. Doehler, Taylor and Smith (2013) investigated to understand the role of statistics in teaching and research by faculty from all disciplines and their perceptions of the statistical preparation of their students. They administered a survey to 747 faculty members from seven colleges and universities regarding the use of statistics in teaching and research with undergraduate students.…”
Section: Theoretical Framework Statistical Literacymentioning
confidence: 99%
“…International Journal of Research in Education and Science (IJRES) 869 guidelines for teaching statistics (e.g., GAISE report), or authors who write textbooks and offer professional development workshops for statistics instructors. Also, Doehler, Taylor and Smith (2013) stressed that it is unknown whether faculty in client disciplines are aware of this guideline. Besides, present study it could be said that instructors could not put statistical literacy at the center of their instruction.…”
mentioning
confidence: 99%
“…This proportion has actually increased recently; in a similar survey conducted in 2001 it was estimated that 52% of instructors viewed statistics as secondary (McAlevey, Everett, and Sullivan 2001). A survey of faculty at seven research institutions and four-year colleges in the southern United States found that 6% of faculty teaching statistics had never actually taken a statistics course themselves (Doehler, Taylor, and Smith 2013).…”
Section: Introductionmentioning
confidence: 99%